Impact of increased risk for fetal aneuploidy on maternal mood: a prospective longitudinal study. (17th August 2016) - Nevay, Dayna L.; Hippman, Catriona; Inglis, Angela; Albert, Arianne; Austin, Jehannine
Abstract: Introduction: Our goal was to prospectively compare the trajectories of depression symptoms through pregnancy and postpartum between women who received normal prenatal screening results and those whose results indicated an increased risk for fetal aneuploidy. Material and methods: Women completed the Edinburgh Postnatal Depression Scale (EPDS) at 4‐week intervals between <26 weeks' gestation and 3 months postpartum. We categorized women into four groups: (i) negative serum screening and ultrasound results (SS − /US −, n = 103), (ii) positive serum screening/negative ultrasound results (SS + /US −, n = 42), (iii) negative serum screening/positive ultrasound results (SS − /US +, n = 19), or (iv) positive serum screening and ultrasound results (SS + /US +, n = 13), and compared EPDS scores between groups using Poisson regression. Results: Women who received any positive prenatal screening result had significantly higher EPDS scores during pregnancy than SS − /US − women ( p = 0.002), with SS − /US + women having the highest scores. During the postpartum, any positive screening test result was only marginally significantly associated with EPDS scores ( p = 0.06), but women in the SS − /US + group had significantly higher scores than women in the SS − /US − group ( p = 0.05). Conclusions: Our data suggest that different types of prenatal screening tests may have different effects on women's moods, and that depression symptoms persist for women who have soft markers identified on ultrasound.